Inovasi Teknologi dalam Kebijakan Lingkungan di Daerah Kabupaten Pelalawan: Peluang dan Tantangan - Ananda, Rizka Gusnia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the application of technological innovations in environmental policies in Pelalawan Regency, Riau Province, focusing on the opportunities and challenges faced. Pelalawan is a region rich in forest and peatland resources but faces serious environmental pressures such as deforestation, land fires, and industrial pollution. Using a qualitative approach and case study methodology, this research identifies various technological innovations that have been implemented, including IoT-based air quality sensors, Geographic Information Systems (GIS) for land monitoring, and the conversion of industrial waste into renewable energy. The findings reveal that these innovations have the potential to enhance environmental management effectiveness but are still hindered by limitations in human resource capacity, bureaucratic resistance, policy fragmentation, and a lack of sustainable funding. The study also highlights the importance of multi-stakeholder collaboration among the government, private sector, and local communities in strengthening technology-based environmental policies. Policy recommendations include strengthening digital infrastructure, revitalizing licensing systems, and improving human resource capacity through technical training. By integrating technological, institutional, and community participation approaches, Pelalawan Regency can serve as a model for sustainable development that balances economic and ecological aspects.